Taxonomic key for the genera of Elmidae (Coleoptera, Byrrhoidea) occurring in Goiás State, Brazil, including new records and distributional notes - Barbosa,Felipe F. (2013)
A taxonomic key for the genera of Elmidae (Coleoptera, Byrrhoidea) occurring in Goiás State, Brazil, including new records and distributional notes. Despite their great diversity and high abundance in Neotropical aquatic environments, the fauna of Elmidae remains practically unknown in some areas and even entire biomes in this region. In this work we bring, for the first time, faunistic data for the Elmidae of central Brazil. The aim of this work was to inventory the Elmidae fauna in central, southwestern and southeastern Goiás State, Brazil and to produce a taxonomic key, at genus level, for adults from the studied region. The taxonomic key presented herein offers means for the identification of all the 13 genera known to occur in Goiás, 11 of them being new records for the State. Moreover, the number of named species registered for Goiás increased from one to nine.